“Análisis De Las Estrategias Metodológicas Aplicadas Para La Enseñanza Del Idioma Inglés Como L2 En Las Universidades De La Ciudad De Babahoyo Y Presentación De Alternativas De Mejoras Para El Desarrollo De Las Destrezas Comunicativas De Los Estudiantes”. - DAHIK SOLIS, CECILIA (2013)
Interest in foreign languages has been of great importance in the years after World War II. The acceleration of economic migration, technological advances in communications and scope that have achieved mass media, today make it a rule more than an exception, that people are able to speak one or more languages besides the acquired at birth. "English is the basic language of books, newspapers, airports and air traffic control, international business, academic conferences, science, technology, diplomacy, sport, international competitions, pop music and advertising. About two-thirds of the world's scientists read in English, and at least three quarters of the electronically stored information is in English. "(Edmundson, W. 2003: 14). There are many ways to learn a language and different methods suit different learning styles. Communicative methods appear to be most promising for most people, but if not well used may be unusable. The design of this manual consists of the theoretical framework in order to generate a range of approaches, methods and techniques, which guide us in the adaptation more appropriate and conducive to the environment that is perceived at the Technical University of Babahoyo, "UTB" and The Autonomous Regional University of the Andes UNIANDES, Babahoyo extension, through a constructivist pedagogical model by competition that underlies the natural method and communicative methodological strategy E.S.A. so that together improve the development of communicative skills earned through English language teaching monitored by the teacher. The philosopher Jeremy Harmer addressed the application of methodological strategies by involving procedural sequence in the orientation of activities and classroom management, lesson planning and its format; Stephen Krashen in the natural approach; while Douglas Brown, Richard and Penny Ur in the development of communication skills since the application of these theories will be favorable and productive in universities students of the respective higher study centers.